Management Modalities of Mandible Fracture and Dental Trauma in Pediatric Patients During Mixed Dentition Phase: A Series of Case Study - Lomtu Ronrang; Alice Lyngdoh (Case Reports in Dentistry)
The prevalence of oromaxillofacial fracture in pediatric patients is comparatively less than in adults, which could be due to several inconclusive factors, such as infrequent exposure to high-contact sports games, rash driving of vehicles and motorbikes, alcohol consumption, and fist fights for personal reasons under the influence of alcohol. More importantly, most of the time, children are under the care of their parents till they reach an age of maturity. One more thing that everyone believes even today is the elasticity nature of their bones as well as their body weight during their growing stage. All these uncertain factors, including the natural way of protection bestowed on us by nature during the childhood stage, might be the actual factors that can easily resist any form of minor trauma in pediatric patients. But sometimes, we come across children who have suffered traumatic head and neck injuries, including mandible fractures, usually falling from a height, and road site accidents while playing on the roadsides, including traffic accidents, which are inevitable. This is a case of three pediatric patients who had experienced accidental dental trauma with slight-displaced mandible fractures with slight dearrangement of normal occlusion and avulsion of permanent teeth. The cases were managed individually according to the types of trauma and injury they had sustained. Among three cases, one was a 9-year-old female pediatric patient, and the other two were male pediatric patients of 7 years old. Clinically, female patients had no mandible fracture as such except avulsion of teeth in the region of 32, 33, and 34. Both the male patients had a slight displacement of the mandible with a dearrangement of occlusion, and one male patient had a bilateral mandible fracture. So considering the nature and type of an injury they had sustained individually, different treatment modalities were employed for each individual as per their requirement for the restoration of normal occlusion, including hard and soft tissues. The prime objectives were the restoration of normal occlusion and alignment of the jawbone, including esthetic and phonetic, without impairing normal growth and development of jawbone and permanent tooth buds. The purpose of this article is to emphasize noninvasive methods of pediatric mandibular fracture reduction, restoration of normal occlusion, and management of soft tissue. Our treatment modalities show that this method can be easily applied in cases of any slightly displaced mandibular fracture in children during mixed dentition periods while taking utmost care of permanent tooth buds compared to other invasive methods of pediatric mandibular fracture management. The application of these various noninvasive treatment modalities and their clinical application for the management of slight displacement of mandibular fractures in pediatric cases were effective and clinically apparent in our study. The study also shows that various treatment modalities employed for the management were acceptable in terms of patient compliance due to noninvasive methods of management for slightly undisplaced mandibular fractures in pediatric cases.